Adsorption efficiency of hydroxyapatite synthesised from black tilapia fish scales for chromium (VI) removal. (2022) - Selimin, M.A.; Latif, A.F.A.; Lee, C.W.; Muhamad, M.S.; Basri, H.; Lee, T.C.
Abstract: Water pollution is a major problem that impacts financial growth and socio-ecological sustainability of a country as well as health of the population. The presence of toxic heavy metals in wastewater such as chromium (Cr) (VI), copper, arsenic, lead, mercury, cadmium, etc. may lead to serious health issues. Therefore, this paper aims to synthesise natural hydroxyapatite (HAp) from black tilapia fish scales and investigate its efficiency as adsorbent for Cr (VI) removal. In this study, the black tilapia fish scales were soaked and washed thoroughly with distilled water to eliminate impurities such as dust and other particles, then dried in the oven before being alkaline treated for 1 h with a 50% NaOH at 100 °C. High purity HAp with an irregular rod-shape was successfully synthesised. The effectiveness of HAp from tilapia fish to remove Cr (VI) was tested at various initial concentrations (30–70 mg/L) and HAp dosages ranging from 2 to 6 g. The results discovered that the synthesised adsorbent had a substantial impact on the removal effectiveness of the Cr (VI) for both manipulated parameters; initial concentration and Cr (VI) pH. The optimum result for Cr (VI) removal rate was achieved at 61.43% at 60 min by using 6 g of HAp. Freundlich isotherm model shows greater suitability with higher R 2 = 0.995. Meanwhile, pseudo-second-order model is favourable for the adsorption process occurred in this study owing to its higher correlation coefficients. According to the findings of this study, black tilapia scale waste can be transformed into an effective adsorbent for Cr (VI) removal in wastewater treatment. This includes industries that may be exposed to Cr (VI), such as welding, coatings, plating, and textile production that use chromium-containing metals.